A review of the factors related to burnout at the early-career stage of medicine. (2nd December 2019) - Hariharan, Thripura Samyuktha; Griffin, Barbara
Abstract: Background : Globally, burnout is an increasingly prevalent problem amongst young medical professionals. This review aims to understand the factors related to burnout in the early-career stage of medicine. Drawing on the widely used Job Demands-Resources Model, the antecedents of burnout were distinguished from its outcomes. Methods: The review adopted the PRISMA guidelines. Using specific search terms, peer-reviewed articles were obtained from a range of databases and assessed against selection criteria. To meet inclusion requirements, the study had to be published between 2000 and 2018, include a validated measure of burnout, and undertake empirical assessment of factors related to burnout in medical students and/or junior medical officers/residents. Additional studies were obtained and reviewed from the reference lists of selected articles. Results: Out of the 3796 studies that were initially found, 585 were assessed against the eligibility criteria leaving 113 studies for review. These studies highlighted the negative consequences of burnout in the early medical career. Also identified were work-specific and person-specific demands that likely lead to burnout and, work and person resources that appear to reduce burnout. Conclusion: This review provides a framework to explain the growing problem of burnout amongst early-career medical professionals. However, further research is necessary to overcome the current reliance on cross-sectional designs and small sample sizes.